Eames [videorecording (DVD)] : the architect and the painter - Franco, James, 1978-; Eames, Charles; Eames, Ray (First Run Features, 2011)
"The husband-and-wife team of Charles and Ray Eames is widely regarded as America's most important designers. Perhaps best remembered for their mid-century plywood and fiberglass furniture, the Eames Office also created a mind-bending variety of other products ... But their personal lives and influence on significant events in American life ... has been less widely understood. Narrated by James Franco, this is the first film dedicated to these creative geniuses and their work"--Container.